Antiparasitic resistance of different populations of ticks (rhipicephalus microplus) in the western of Santa Catarina State, Brazil Resistência antiparasitária de diferentes populações de carrapatos (rhipicephalus microplus) no oeste do estado de Santa Catarina, Brasil - Pazinato R.* (2014)
Background: In Brazil, the tick Rhipicephalus microplus is a serious problem for beef and milk cattle due to the damage caused directly to the animal. Ticks are responsible for major economic losses related to production, especially in breeds of European origin, prevalent in Southern Brazil. The use of most acaricides may allow the survival of some tick that transmits this characteristic to future generations, consequently each successive treatment is a process of selection. The lack of technical guidance on how to control ticks may contribute to the emergence of new resistant strains of ticks. The objective of this study was to test the efficacy of antiparasitic drugs on tick populations (Rhipicephalus microplus) from the Western region of Santa Catarina, Brazil. Materials, Methods & Results: Thirty-one farms participated in this study and 70 engorged female ticks were collect from each property. They were divided into seven groups of 10 specimens each. Ticks were exposed to six commercial drugs: amitraz (A); cypermethrin, chlorpyrifos, and citronellal (B); diazinon (C); diclovós and chlorpyrifos (D); cypermethrin (E); cypermethrin, chlorpyrifos, and piperonyl butoxide (F); and one group was used as a control to validate the test (G: no drug). Tests with acaricides followed standard protocols, recommended for in vitro testing. The effectiveness of the product was calculated based on egg laying and hatching. The drug tested is considered effective if the result was more than 95%. The number of farms with populations of resistant ticks were 13 (41.9% - group A), 2 (6.45% - group B), 15 (48.38% - group C), 6 (19.35% - group D) and 12 (38.7% - group E). Ticks from the group F did not show resistance to the tested products. i.e., all farms obtained 100% efficiency. Among the products tested that showed the highest efficacy were the combinations of three or two active principle as cypermethrin, chlorpyrifos and piperonyl butoxide (group F - 100%), cypermethrin, chlorpyrifos and citronella (group B - 99.04%), and dichlorvos and chlorpyrifos (group D - 92.53%). However, products with only one active principle showed lower efficiency such as amitraz (group A - 87.94%), diazinon (group C - 70.71%), and cypermethrin (group E - 73.15%). Discussion: These results are very similar to other studies conducted recently in different Brazilian regions, but unknown in Western Santa Catarina, which currently has the largest dairy herd in the Santa Catarina State. In this study it was found that farmers are unaware of important tests to control tick, like the immersion test of engorged females that contributes to parasite control, identifies ineffective drugs and reduces labor costs. As researchers reported the inappropriate use of antiparasitic drugs like subdosage or superdosage, and the high frequency of acaricide use, may select and propagate the occurrence of resistance selection pressure. Therefore, it is concluded that the resistance of ticks is a problem present in the majority of the Western Santa Catarina properties. The current study shows that 81.7% of the tested tick population of parasitic resistance presented to one or more drugs. This study found that the cattle farmers were not aware of tests that detect ticks susceptibility to acaricides and did not adopt proper technical procedure when using chemicals. These indicate the need to educate cattle farmers on considering resistance as criteria, considering efficiency and cost of the treatment.